Policymakers’ horizon and trade reforms: the protectionist effect of elections - Conconi, Paola; Facchini, Giovanni; Zanardi, Maurizio (Elsevier, 2014)
This paper shows that electoral incentives deter politicians from supporting trade liber- alization. We focus on all major trade liberalization bills introduced since the early 1970s in the U.S. Congress, in which House and Senate members serve respectively two- and six-year terms and one third of senators face elections every two years. We show that senators are more likely to support trade liberalization than House representatives. How- ever, this result does not hold for the last generation of senators, who face elections at the same time as House members, suggesting that inter-cameral differences are driven by term length. Considering senators alone, we find that the last generation is less likely to support trade liberalization than the previous two. This result is pervasive and holds both when comparing the behavior of different senators voting on the same bill and that of individual senators voting on different bills. The protectionist effect of election proximity disappears for senators who are retiring or hold safe seats.